2022
DOI: 10.1080/21642850.2022.2158831
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory emotional self-efficacy and anxiety in times of pandemic: a gender perspective

Abstract: Objectives The COVID-19 pandemic and resultant lockdown and containment measures have instigated substantial changes in our daily lives and have affected many people’s mental health. This paper reports two studies exploring gender-based differences with regard to the impact of COVID-related confinement on individuals’ self-efficacy to regulate negative emotions (RESE-NE) and anxiety. Methods: Study 1 (cross-sectional; 269 participants; 52% women) explored the evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The pandemic has had serious consequences related to mental health (Ausín et al, 2021;Brooks et al, 2020;Cuadrado et al, 2021;Cuadrado, Rich-Ruiz et al, 2023;González-Sanguino et al, 2021;Meng et al, 2023;Sicouri et al, 2023;Tull et al, 2020;Wang et al, 2020). The question is, can the perceived efficacy of COVID-19 prevention measures act as a moderating variable of these effects, specifically in the face of stress and depression?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic has had serious consequences related to mental health (Ausín et al, 2021;Brooks et al, 2020;Cuadrado et al, 2021;Cuadrado, Rich-Ruiz et al, 2023;González-Sanguino et al, 2021;Meng et al, 2023;Sicouri et al, 2023;Tull et al, 2020;Wang et al, 2020). The question is, can the perceived efficacy of COVID-19 prevention measures act as a moderating variable of these effects, specifically in the face of stress and depression?…”
Section: Discussionmentioning
confidence: 99%
“…In several countries, governments declared stay-at-home orders due to the public health emergency, limiting social activity and applying general homeconfinement rules, usually excepting travel for essential jobs (Cohen & Kupferschmidt, 2020). The confinement and situation of stay-at-home orders have been associated with decreased mental health (Ausín et al, 2021;Brooks et al, 2020;Cuadrado et al, 2021;Cuadrado, Rich-Ruiz et al, 2023;González-Sanguino et al, 2021;Tull et al, 2020;Wang et al, 2020), with significant increases in stress and depression suffered by individuals. This decrease in mental health, in com-parison to the pre-pandemic state, has been seen as a consequence of both social limitations and a decrease in the practice of healthy habits related to diet, physical exercise, and sleep during confinement (Ammar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In medical contexts, strong self-efficacy can help reduce anxiety, improve healthcare decisionmaking, and increase general well-being 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In short, high levels of self-efficacy are associated with low levels of anxiety. Furthermore, several studies have shown that self-efficacy acted as a protective factor for mental health during lockdown periods [31][32][33][34]66,91]. In addition, self-efficacy proves crucial in overcoming particularly traumatic events [92,93].…”
Section: The Role Of Self-efficacy As a Protective Factor Of Mental H...mentioning
confidence: 99%
“…Very little data is currently available on the mental health of individuals once the restrictions have ended or on the relationship between mental health and days of lockdown [6]. Notably, according to some studies, high levels of self-efficacy play a key role in preserving the mental health of individuals during lockdown [31][32][33][34]. Self-efficacy is defined as the perception of one's own ability to succeed in specific situations or accomplish a task [35,36].…”
Section: Introductionmentioning
confidence: 99%